Utilization of Emergency Department Services by the Bedouin Population in Southern Israel - Arnon Dov Cohen; Jacob Dreiher; Amir Sharf; Daniel Aharon Vardy (The Scientific World Journal)
Excessive use of the emergency department (ED) is associated with increased costs and workload in the ED, patients' inconvenience and disruption of the continuity of care. The study's goal was to describe trends in ED utilization among Bedouins living in southern Israel. A retrospective cross-sectional study was conducted in primary care clinics in southern Israel. Patients included Bedouin and Jewish patients insured by Clalit Health Services. Data was retrieved from a central database. The number of visits to the ED and age-adjusted rates of ED visits during 2000-2003 were determined in the Bedouin vs. Jewish population. All visits that ended in hospitalization were excluded. Data was stratified according to patients' residence (semi-nomadic vs. urban Bedouins) and referral origin. Age-adjusted rates of ED visits decreased from 42.9/1000 patients/month in 2000 to 38.3/1000 patients/month in 2003. There were more ED visits in the Bedouin as compared to Jewish population (38.3/1000 vs. 21.8/1000 patients/month). The decrease in ED utilization was more prominent among adult semi-nomadic Bedouins (from 60.8/1000 to 40.3/1000 patients/month). The proportion of referrals by the family physician to ED significantly decreased (among urban Bedouins: from 54.3% to 43.2%, p<0.001; among semi-nomadic Bedouins: from 53.9% to 39.9%, p<0.001), while the proportion of selfreferrals and referrals from physicians other than the family physician increased. A decrease in ED utilization by the Bedouin population during the last years was demonstrated. Utilization of ED services is still increased as compared to the non-Bedouin population. Interventions to control excessive use of ED services in the Bedouin population are currently underway.